SYSTEM OF RECOMMENDATIONS FOR FORMING THE PORTFOLIO OF SECURITIES ON THE RUSSIAN AND FOREIGN EXCHANGE MARKETS (International Journal of Innovative Technologies in Economy, 2018)
There is a comprehensive analysis of selected shares (both foreign and domestic) was conducted on the basis of the methodology for the formation and management of the securities portfolio using up-to-date statistical data in the article. This allowed the author to obtain results that have scientific novelty and practical significance. The research was conducted under the supervision of Professor Tatyana Burtseva, Professor of the Department of Social and Economic Sciences, Ph.D., Associate Professor.